Relationship between Geriatric Nutritional Risk Index with all-cause and CVD mortality in osteopenia and osteoporosis - Guo, Tianting; Feng, Haorong; Xiong, Lijiao; Mo, Jianwen; Zhang, Xiaoan; Xie, Junbin; Hu, Hongkai (Frontiers in Public Health, 2024)
PurposeThis study investigated the relationship between Geriatric Nutritional Risk Index (GNRI), and all-cause, cardiovascular (CVD) mortality, in individuals with osteopenia and osteoporosis.MethodsUsing NHANES data from 2005 to 2019, 6,824 participants diagnosed with osteopenia and osteoporosis were analyzed. Participants were categorized based on GNRI tertiles, and statistical methods like the fitted curves, Kaplan-Meier curves, cox regression, and subgroup analyses were employed.ResultsLower GNRI tertiles correlated with older age, male gender, and more comorbidities. Mortality rates differed significantly across GNRI tertiles over an average 7.9-year follow-up, with a notable inverse J-shaped association between GNRI and mortality. Adjusted HRs indicated a 1.6-2-fold increase in all-cause mortality for the lowest GNRI tertile, persisting across comprehensive adjustments. CVD mortality followed a similar trend.ConclusionsThis study illuminates a robust correlation between GNRI levels and mortality risks in osteopenia and osteoporosis. Its consistent dose-response relationship across all-cause, and CVD mortality underscores its pivotal role as a prognostic factor.